PENGARUH BUDAYA KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI KANTOR CAMAT SUNGAI RAYA KABUPATEN KUBU RAYA - Fajjar Fahdiansyah E.42008076 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
Abstract Abstract : The title of this research is "The Effect of Work Culture to Performance of Civil Servants In Sungai Raya District Office in Kubu Raya Regency. This research is supposed to know whether work culture affects the performance of the Civil Servants Sungai Raya District Office in Kubu Raya Regency.  The title of this research  concerns was brought up based on the evolving work culture affects the performance of civil servants in the ministry. This research is quantitative research using simple  linear  regression  statistical  test. Based  on the results  of the study, obtained  the following regression equation: Y = 6.611 + 0444 X Based on the analysis of statistical data, indicators in this study are valid and variables are reliable. The results indicate that the hypothesis Fcount  greater than F table  (9.454> 4.45) with a significance level of 0.456 so that the hypothesis in this study accepted that there is a positive and significant correlation between work culture to performance of civil servant. Key Word : Work Culture and Performance of Civil Servant